RELASI ANTARA KEBIJAKAN PEMERINTAH BIDANG EKONOMI DENGAN KINERJA PENDIDIKAN DI KABUPATEN SINJAI - Ilyas, Ilyas; Firman, Akmad; La Ode Anto, La Ode Anto; Dwiputri, Inayati Nuraini; Isalman, Isalman (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to find the relationship between government policies in education and education performance in Sinjai District. The research method used is quantitative research. The main data source comes from the publication of the Central Statistics Bureau (BPS) of Sinjai Regency and other publications related to writing. Analysis of the data used is quantitative descriptive. The results of the analysis show that government policies are very influential or have a positive relationship to improving educational performance. This study also shows that the performance of education in Sinjai District as seen from the Human Development Index (HDI) component in the last five years (2014-2018) has increased, although it is still slow. The still increase in HDI in Sinjai Regency requires the Regional Government to formulate various strategies, create programs and formulate policies that are truly able to accelerate the improvement of educational performance in the Sinjai Regency Keywords: Government Policy, Economy, Education Performance, HDI.